Impact of operator experience and training strategy on procedural outcomes with leadless pacing: Insights from the Micra Transcatheter Pacing Study - El-Chami, Mikhael; Kowal, Robert C; Soejima, Kyoko; Ritter, Philippe; Duray, Gabor Z; Neuzil, Petr; Mont, Lluis; Kypta, Alexander; Sagi, Venkata; Hudnall, John Harrison; Stromberg, Kurt; Reynolds, Dwight (Pacing and clinical electrophysiology, 2017)
BACKGROUND: Leadless pacemaker systems have been designed to avoid the need for a pocket and transvenous lead. However, delivery of this therapy requires a new catheter-based procedure. This study evaluates the role of operator experience and different training strategies on procedural outcomes. METHODS: A total of 726 patients underwent implant attempt with the Micra transcatheter pacing system (TPS; Medtronic, Minneapolis, MN, USA) by 94 operators trained in a teaching laboratory using a simulator, cadaver, and large animal models (lab training) or locally at the hospital with simulator/demo model and proctorship (hospital training). Procedure success, procedure duration, fluoroscopy time, and safety outcomes were compared between training methods and experience (implant case number). RESULTS: The Micra TPS procedure was successful in 99.2% of attempts and did not differ between the 55 operators trained in the lab setting and the 39 operators trained locally at the hospital (P = 0.189). Implant case number was also not a determinant of procedural success (P = 0.456). Each operator performed between one and 55 procedures. Procedure time and fluoroscopy duration decreased by 2.0% (P = 0.002) and 3.2% (P < 0.001) compared to the previous case. Major complication rate and pericardial effusion rate were not associated with case number (P = 0.755 and P = 0.620, respectively). There were no differences in the safety outcomes by training method. CONCLUSIONS: Among a large group of operators, implantation success was high regardless of experience. While procedure duration and fluoroscopy times decreased with implant number, complications were low and not associated with case number. Procedure and safety outcomes were similar between distinct training methodologies.
Keywords: kardiostimulátor; leadless pacemaker; Equipment Failure Analysis; Humans; Clinical Competence; srdeční katétry; Equipment Design; Female; Aged; learning curve; výsledek terapie; Cardiac Pacing, Artificial; senioři; lidé; klinické kompetence; procedure training; outcomes; bezpečnost pacientů; ženské pohlaví; Male; srdeční arytmie; Treatment Outcome; design vybavení; Patient Safety; clinical trial; Arrhythmias, Cardiac; Cardiac Catheters; kardiostimulace umělá; mužské pohlaví; analýza selhání vybavení; Pacemaker, Artificial